Karen Thompson and Tom Nolan. - Sahl, Ted (photographer):::Creator::::::::::::
Karen Thompson autographs a copy of her book, "Why Can't Sharon Kowalski Come Home?" for San Mateo County Supervisor Tom Nolan at a BAYMEC event in her honor.